Can a fifty percent increase in public sector wages improve the position of public sector employees in the long run? An assessment of the public-private income gap in Hungary - Szilvia Hámori; Anna Lovász (Hungarian Academy of Sciences, Institute of Economics, 2011)
We provide a detailed descriptive analysis of the long-term effects of the 50 percent public sector wage increase initiated by the government in 2002 in order to improve the relative situation of public sector workers. The aim of this policy was to attract high quality workers to the public sector, and to counteract the problem of "brain drain," the loss of high-skilled workers to abroad. To study the effects on the public-private income gap - and on high-skilled workers in particular - we employ empirical methods that allow us to take differences in the entire wage distribution (quantile regressions), workforce and firm composition (decomposition), as well as various potential biases (corrections for underreported wages and workplace characteristics) into account. Our results indicate that there is a large income premium in favor of the private sector at the higher end of the income distribution, especially once we account for worker and firm characteristics, which suggests that the same person earns substantially less in the public sector. This is especially pronounced for high-skilled workers. The 50 percent increase initially improved the relative income of public sector workers, but in the longer run, income gaps returned to close to the pre-reform level and the distributional differences remained.
Keywords: C21; J31; J45; 330; quantile decomposition; wage level and structure; public-private pay gap; Vergütungssystem im öffentlichen Dienst; Lohnstruktur; Privatwirtschaft; Ungarn